1996
DOI: 10.1046/j.1360-0443.1996.9157117.x
|View full text |Cite
|
Sign up to set email alerts
|

The Amsterdam Methadone Dispensing Circuit: genesis and effectiveness of a public health model for local drug policy

Abstract: During the 1970s, the Methadone Dispensing Circuit (MDC) was initiated by the municipality of Amsterdam in order to cope with the heroin addiction epidemic that afflicted the city. In the MDC, methadone is dispensed to opiate addicts on a maintenance basis in low-threshold public health programmes, as well as in high-threshold treatment programmes. The MDC is an essential part of the local drug policy in the city. It is designed to get in touch with all opiate addicts who are not able to manage their lives in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Providing combination HIV-prevention to IDUs under one umbrella, in a point-of-care, one-stop venue that addresses their myriad needs may seem like a Holy Grail, but it is ultimately what substance users need and is likely to be cost-effective. For decades, Amsterdam has offered integrated OST, HIV and primary care services for substance users (40). In the U.S., some early steps have been made to promote a multi-city infrastructure that integrates HIV primary care and substance abuse treatment (41).…”
Section: Resultsmentioning
confidence: 99%
“…Providing combination HIV-prevention to IDUs under one umbrella, in a point-of-care, one-stop venue that addresses their myriad needs may seem like a Holy Grail, but it is ultimately what substance users need and is likely to be cost-effective. For decades, Amsterdam has offered integrated OST, HIV and primary care services for substance users (40). In the U.S., some early steps have been made to promote a multi-city infrastructure that integrates HIV primary care and substance abuse treatment (41).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated the efficacy of methadone maintenance therapy (MMT) in decreasing illicit drug consumption and criminal behavior, improving the rehabilitation of intravenous opiate-addicted patients, and lowering the prevalence of HIV infection (Newman, 1987;Plomp, Van der Hek, & Ader, 1996;Schottenfeld & Kleber, 1995). However, MMT is associated with several problems, including limited patient and community acceptance, and it appears not to be optimal for all subjects (Kolar, Brown, Weddington, & Ball, 1990;Schoenbaum & Selwyn, 1995 Since 2001, buprenorphine (BUP), an opiate A-receptor partial agonist, has been available for the treatment of heroin addiction, proving to be effective in reducing cravings for opiates and in blocking withdrawal symptoms, thus representing a useful alternative drug to methadone (Cozzolino et al, 2002(Cozzolino et al, , 2003Ling et al, 1998;Pani, Maremmani, Pirastu, Tagliamonte, & Gessa, 2000).…”
Section: Introductionmentioning
confidence: 98%
“…17 The Amsterdam methadone maintenance system aims to keep in contact with as many drug users as possible through different types of programs (low, medium, and high threshold) that provide methadone in combination with social-medical care and needle-exchange facilities. 18,19 These programs involve no waiting lists, and it is relatively easy to enter and reenter the programs. Ongoing drug use during treatment is tolerated in low-and mediumthreshold programs.…”
mentioning
confidence: 99%